Rhetorical Device Analysis On Stand Up Comedy In Kompas Tv - Hardiyanti, Selvi (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This study deals on the rhetorical analysis of Stand-up Comedy program in Kompas TV. It was aimed to investigate the rhetorical elements and describe howthe rhetoric used by the three Stand Up comedians (Ridwan, Dany, and Mamat) inStand Up Comedy Indonesia (SUCI) Kompas TV. Descriptive qualitative method was used to describe, identify, and classify the data obtain from the scripts by using Brooks and Warrens theory in Tara Lockharts journal which focusing onthe modern rhetoric books that centre in chapter of style: style, diction, and figurative language. Based on finding in this study, analyzing types of style,diction and figurative language in Stand Up Comedy in Kompas TV, it was found that the type abstract was 22 (32.35%), followed by style type whit the percentage was 3 (4.41%), connotative type 4 (4.88%), specific type 11 (16.17%), concretetype 6 (8.82%), denotative type 4 (5.88%), denotation type 2 (2.94%), hyperbole type 7 (10.29%), synecdoche type 3 (4.41%), metonymy type 3 (4.41%),oximoron type 2 (2.94%), and smile type 1 (1.47%). There fore, it can be infer that the stand-up comedian using the same types of diction and almost the same type sof figurative language but the differences between them is delivering their rhetoric. The implication of this study is to improve rhetoric analysis with using correct diction and accuracy of figurative language.